China-Pakistan Economic Corridor: Meeting Security Challenges in Balochistan Through Trade and Development - Hashmat Ullah Khan; Shan Yu (Vestnik MGIMO-Universiteta)
The article explores the prospects of the China-Pakistan Economic Corridor (CPEC) for developing the Balochistan province of Pakistan. Balochistan is the largest province of Pakistan, full of natural resources; it has geostrategic importance due to its location, long coastal line, Gwadar port, and the recently launched CPEC project. It remains an economically underdeveloped and socially and politically marginalized province, facing extensive poverty and lack of economic opportunities despite the enormous economic potential, separatism movements, terrorism, and severe clashes with the federal government over its financial share in the state's divisible pool and natural resources found in the province. Economic backwardness is one of the main reasons behind the critical challenges in the province. In this regard, it is essential to analyze the prospects of CPEC projects for the province's economic, social, and political redevelopment and how CPEC can improve the security situation and resolve the separatist movements in the province. CPEC provides potential opportunities for improving the economic and security situation in the province and the region on the whole, as it brings a huge amount of Chinese foreign direct investment to the province, creates jobs, encourages infrastructure development, establishes special economic zones, and turns the province into a corridor of regional trade connecting it with other economies. The article substantiates that CPEC has prospects to cool down the Baloch uprising, bring peace, prosperity, and stability, solve the economic crises, decrease poverty and improve the country's living conditions and region.